1997
DOI: 10.1007/s002130050296
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neurochemical characteristics of phentermine and fenfluramine administered separately and as a mixture in rats

Abstract: Clinical case studies suggest that combined administration of the serotonergic agent fenfluramine (FEN) and the weak amphetamine-like anorexic agent phentermine (PHEN) may be useful in the treatment of alcohol and cocaine addictions. The present experiment examined the nature of the interaction between the two agonists using the drug discrimination paradigm. In vivo microdialysis served to examine the neurochemical profile of dopamine and serotonin release in the nucleus accumbens. In conscious rats, acute inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 29 publications
6
30
1
Order By: Relevance
“…10 The potent 5HT-releasing action of fenfluramines noted in the hypothalamus (Gundlah et al 5 and present data), the striatum 16 and in the nucleus accumbens 13,15 has also been demonstrated using blood platelets. 22,23 This could provide a peripheral source of 5HT that is sufficient to play a role in the genesis of valvulopathy.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…10 The potent 5HT-releasing action of fenfluramines noted in the hypothalamus (Gundlah et al 5 and present data), the striatum 16 and in the nucleus accumbens 13,15 has also been demonstrated using blood platelets. 22,23 This could provide a peripheral source of 5HT that is sufficient to play a role in the genesis of valvulopathy.…”
Section: Discussionsupporting
confidence: 69%
“…Similar additive effects have been shown between phentermine and fenfluramine on both 5HT and dopamine levels in the nucleus accumbens. 13 In the striatum, however, evidence has been obtained for a synergistic interaction between phentermine and fenfluramine since the minimal impact of phentermine alone on striatal 5HT levels was nevertheless reported to enhance that caused by fenfluramine when the two drugs were given in combination. 16 In determining whether the interactions between phentermine and=or fenfluramine are additive, synergistic or even antagonistic, it is likely that regional differences in the sensitivity of 5HT and other systems to the drugs need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…24 -27 The increase in synaptic levels of serotonin in the hypothalamus stimulates the secretion of PRL. The dose of FEN used in the present study is within the reported range of doses that produce dose-dependent increases in synaptic serotonin levels 19,28 and plasma PRL levels. 20,21 The increase in plasma PRL levels after FEN is blocked either by pretreatment with serotonin receptor antagonists or reuptake inhibitors 16,17,20,21,23,29 or lesions of the raphe nuclei.…”
Section: Discussionsupporting
confidence: 53%
“…Phentermine is a structural analogue of d-amphetamine that has been used as an anti-obesity agent in the USA for over 30 years. Phentermine's weight-loss action was initially ascribed to its sympathomimetic properties involving NA and DA (Samanin et al, 1975), but in later years the dopaminergic component of phentermine has been largely overlooked (Cerulli et al, 1998;Finer, 1997); this is despite recent in vivo evidence to show that phentermine does activate the dopaminergic system Shoaib et al, 1997). d-Amphetamine was one of the first drugs to be widely employed for management of obesity, but its use is no longer recommended due to the abuse potential of the drug (Cerulli et al, 1998).…”
Section: Discussionmentioning
confidence: 85%